Comparison of standard balloon and drug-coated balloon angioplasty in patients with the below-the-knee peripheral artery disease - Kaygin,Mehmet Ali (2021)
SUMMARY OBJECTIVE: The objective of this study was to compare the interventions of percutaneous transluminal drug-coated balloon angioplasty (DCB PTA) and standard PTA in the treatment of patients with the below-the-knee peripheral artery disease (BTK PAD). METHODS: Overall, 196 patients (113 males and 83 females; mean age: 63.56±11.94 years; 45–83 years) were treated with PTA for BTK PAD between June 2014 and March 2019. RESULT: Standard PTA (group 1; 96 patients) and DCB PTA (group 2; 100 patients) results were analyzed and compared retrospectively. No statistically significant difference was found between the mean ages of group 1 and 2 patients (p=0.371, p>0.05). Demographic and clinical data were compared and no any statistically significant differences was found between the two groups. Comparing in terms of the iliac lesion, there was no statistically significant difference between the two groups. However, a statistically significant difference was found between the two groups in terms of frequency of popliteal lesions (p=0.001; p<0.05). There was not a statistically significant difference between the two groups in terms of other lesions. In addition, limb salvage rates were 82.0% (18 amputations) and 65.6% (33 amputations) in the drug-release balloon group and the naked balloon group, at the end of 1 year, respectively. No distal embolism, limb-threatening ischemia, and mortality were observed in any patients. CONCLUSIONS: Based on this study, patients in the DCB group had significantly higher rates of primary patency as compared with the other patients.